High infestation by Rhipicephalus (Boophilus) microplus in a mare: A rare case report - Volpato A.* (2013)
Rhipicephalus (Boophilus) microplus is a natural parasite of cattle, with rare reports of parasitism in horses. Therefore, the aim of this study is to report a rare case of high infestation by R. (B.) microplus in a mare in the town of Riqueza, state of Santa Catarina, Southern Brazil. In December 2012, in a farm with 12 horses in its herd, a single mare was highly infected, showing clinical signs such as pale to pink mucous membranes and bleeding in the neck, the main place in her body where the ticks were fixed. The horse was treated through the use of a spray with a drug association of cypermethrin, chlorpyrifos, and citronellal (Colosso®), showing temporary effectiveness, since 15 days posttreatment immature forms (larvae and nymphs) of ticks were again found. Therefore, this mare has high susceptibility to parasitism by R. (B.) microplus, differently from the other horses at the same farm that were not parasitized by this mite. © 2013 Springer-Verlag London.